Offenders index cohort data, 1953-1997 (UK Data Service, 2018)
The data were drawn from the Home Office Offenders Index to provide estimates of the prevalence of offending (as measured by convictions for 'Standard List' offences) in the population of England and Wales. Results were last reported in detail in the Home Office Statistical Bulletin 14/95 Criminal careers of those born between 1953 and 1973 (1995). One of the main results reported is that an estimated 34% of men and 8% of women had at least one conviction for a Standard List offence before the age of forty. The percentage of males with a custodial sentence before the age of forty is 7% and females less than 1%. The cohort data includes information on court appearances and convictions for individual anonymised offenders. As such it provides a resource for investigating patterns of convictions for known offenders and modelling their interaction with the criminal justice system.